2020
DOI: 10.1103/physrevx.10.011068
|View full text |Cite
|
Sign up to set email alerts
|

Nanotribology of Ionic Liquids: Transition to Yielding Response in Nanometric Confinement with Metallic Surfaces

Abstract: Room-temperature ionic liquids (RTILs) are molten salts which exhibit unique physical and chemical properties, commonly harnessed for lubrication and energy applications. The pure ionic nature of RTIL leads to strong electrostatic interactions among the liquid, furthermore exalted in the presence of interfaces and confinement. In this work, we use a tuning-fork-based dynamic surface force tribometer, which allows probing both the rheological and the tribological properties of RTIL films confined between a mill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(66 reference statements)
2
12
0
Order By: Relevance
“…By assuming that the surface energies of evaporated gold/air and of ns-Au/air are comparable, the results obtained on the gold surfaces reinforce the hypothesis that the IL transition to a solidlike phase is promoted by a higher surface energy of the liquid phase compared to the solid one, as also demonstrated in Refs Comtet et al (2017) and Lainé et al (2020), which is associated to a lower wettability of the liquid phase on the confining surface (Evans, 1990).…”
Section: Solid-like Ionic Liquid Structuressupporting
confidence: 77%
See 1 more Smart Citation
“…By assuming that the surface energies of evaporated gold/air and of ns-Au/air are comparable, the results obtained on the gold surfaces reinforce the hypothesis that the IL transition to a solidlike phase is promoted by a higher surface energy of the liquid phase compared to the solid one, as also demonstrated in Refs Comtet et al (2017) and Lainé et al (2020), which is associated to a lower wettability of the liquid phase on the confining surface (Evans, 1990).…”
Section: Solid-like Ionic Liquid Structuressupporting
confidence: 77%
“…Recent works (Comtet et al, 2017;Lainé et al, 2020) describe phase transition of confined IL between conductive interfaces into a glassy-like state. This behavior is interpreted in terms of a freezing transition shift, which is related to the surface energy of the liquid with respect to the confining surface.…”
Section: Solid-like Ionic Liquid Structuresmentioning
confidence: 99%
“…1,[35][36][37] The dynamic behaviors of nanoconned ILs have also been investigated by SFA and colloidal AFM as the viscosity and phase response of these uids in conned geometry strongly affect the lubricating property of these uids. 1,11,36,38,39 In the last decade, an increasing number of studies also evaluated the structures and physico-chemical properties of imidazolium-and pyrrolidinium-based ILs as a function of hydrostatic pressure. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Zhao et al employed molecular dynamics (MD) simulations to investigate the effect of pressure on the interionic interactions of 1-butyl-3-methylimidazolium hexa-uorophosphate ([C 4 mim][PF 6 ]) IL and provided evidence for changes in the conformation in the alkyl chains of cations at high pressure (0.6 GPa).…”
Section: Introductionmentioning
confidence: 99%
“…This important finding provides a microscopic picture for recent experimental results in which capillary freezing and wetting of an ionic liquid was found to be promoted by metal surfaces. 5,6 In particular, these authors showed that the freezing point shift upon varying λ could be rationalized by assuming that the difference between the liquid/wall and crystal/wall surface tensions scales with the density difference between the crystal and liquid. 5…”
Section: Capacitancementioning
confidence: 99%
“…liquids display a wealth of unexpected fundamental behaviors -in particular in confinement. Beyond now well-documented adsorption, overscreening and crowding effects [1][2][3] , recent experiments have highlighted novel phenomena such as unconventional screening 4 and the impact of the electronic nature -metallic versus insulating -of the confining surface on wetting/phase transitions 5,6 . Such behaviors, which challenge existing theoretical and numerical modeling frameworks, point to the need for new powerful tools to embrace the properties of confined ionic/dipolar liquids.…”
mentioning
confidence: 99%